Sustainability Consciousness Questionnaire - long version (SCQL) - Olsson, Daniel (Karlstad University, 2017)
This dataset includes different versions of the long 50 items version of the sustainability consciousness questionnaire (SCQL). The versions are:
- grade six, 12-13 years old students (English and Swedish)
- grade nine, 15-16 years old students
- grade twelve, 18-19 years old students
- Chinese version (grade six and high school)

The file SC-instrument is the the categorization of the items in the long version of the sustainability consciousness questionnaire (SCQL). All age adapted versions have the same categorization.

The dataset was originally published in DiVA and moved to SND in 2024.
Sustainability Consciousness Questionnaire - long version (SCQL)
Keywords: young people; ungdomar; environmental attitudes; miljöattityder; sustainable development; hållbar utveckling; Biology; Biologi; Biological Sciences; Biologi